Economic modeling and prediction of Summer Olympics medal wins and FIFA world cup semi-finalists - Andreff, W. (2010)
In one of the few articles about the sports economy in developing countries (Andreff, 2001), it has been empirically verified that the number of medals that a country can make at Summer Olympics significantly depends on its population and GDP per inhabitant. At the crossroads between development economics and sports economics, another issue nearly remains unheeded so far: it is how a nation level of economic development may impact on its sport performance at the soccer (football) FIFA World Cup while the same topic about Summer Olympics has been increasingly elaborated on in existing economic literature. The latter is based on econometric estimation of how much significant are the economic determinants of medal wins by each participating nation. A same methodology starts developing for other mega sport-events such as international cricket tournaments (Choudhury et al., 2007) and athletics as a specialised component of Summer Olympics (Heyndels and Du Bois, 2006), but not much as regards to FIFA World Cup. Our research question is: would a model based on economic determinants that is used for successfully predicting the distribution of medal wins at Olympic Games be able to provide an econometric prediction of major FIFA World Cup sporting outcomes? We would respond the aforementioned question as follows. We start with briefly reminding the most interesting methodologies at work in estimating and predicting Summer Olympics medal distribution (1). Then we show how our own model has resolved the issue and predicted how many medals each nation has obtained at the 2008 Beijing Olympics (2). Thereafter, we go on comparing our prediction to actual outcomes of different nations in Beijing and to other prospective econometric studies on the same topic, a comparison which is absolutely rare in the literature so far (3). At this stage, it is necessary to understand why a similar prediction model has not yet developed regarding FIFA World Cup: a major reason is that the soccer World Cup outcome is rather unpredictable, not only due to high uncertainty of outcome, but because each FIFA World Cup final tournament is characterised by a number of "surprises" (4). Then we present how to adapt our model of Olympic medal prediction to FIFA World Cup by introducing, alongside with economic variables, some football-specific or "footballistic" variables (5). A model is estimated on the basis of FIFA World Cup results from 1962 to 2006 (6), and then used to provide a prediction of the semi-finalists at the 2010 World Cup in South Africa (7). We conclude with a pinch of salt about the interpretation of such a prediction exercise since, compared with the actual outcome of the 2010 World Cup, our prediction, as all other predictions in this area, does not exhibit very good results (8). This opens an avenue for further economic research about the notion of "surprise" or surprising (unexpected) outcome of a sport contest.